2013
DOI: 10.1037/a0030956
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to interpersonal violence and its associations with psychiatric morbidity in a U.S. national sample: A gender comparison.

Abstract: Objectives We examine gender differences in population rates of various types of interpersonal violence in a U.S. national sample and investigate gender as a moderator of the associations between interpersonal violence and lifetime mental disorders and suicide attempts. Methods Data were drawn from the National Comorbidity Survey-Replication study; 5,692 women and men completed interviews assessing lifetime exposure to nine types of interpersonal violence, Diagnostic and Statistical Manual of Mental Disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 56 publications
9
98
1
2
Order By: Relevance
“…The HITS screening tool 13 comprises the following four items: "Over the last 12 months, how often did your partner: (1) physically hurt you, (2) insult you or talk down to you, (3) threaten you with harm, and (4) scream or curse at you?" Responses are scored on a 5-point scale from 1 ("never") to 5 ("frequently") and summed for a total score (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Findings support the concurrent validity of this instrument.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…The HITS screening tool 13 comprises the following four items: "Over the last 12 months, how often did your partner: (1) physically hurt you, (2) insult you or talk down to you, (3) threaten you with harm, and (4) scream or curse at you?" Responses are scored on a 5-point scale from 1 ("never") to 5 ("frequently") and summed for a total score (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Findings support the concurrent validity of this instrument.…”
Section: Methodsmentioning
confidence: 91%
“…[2][3][4] Similarly, IPV increases risk for psychiatric conditions such as posttraumatic stress disorder (PTSD), other anxiety disorders, depression, substance misuse, eating disorders, and suicidality. [3][4][5] Relative to civilians, female veterans are at higher risk for physical and sexual forms of IPV (33.0 % vs. 23.8 % lifetime prevalence). 2 Although the reasons for elevated risk among female Veterans remain unknown, some theorize that women's exposure to violence-prone environments, such as violent childhood homes and the military, may elevate women's risk for IPV.…”
mentioning
confidence: 99%
“…11,16 Among noncollege adult populations, interpersonal victimization consistently predicts negative health outcomes, including suicidal behavior. 8,[17][18][19][20] Indeed, World Health Organization data indicate that interpersonal violence, including sexual assault, has the most robust and consistent association with suicide ideation and suicide attempts across nations, even after considering other factors. 20 Using data from the National Comorbidity Survey-Replication, Iverson and colleagues found that respondents with a history of rape have nearly twice the risk of suicide attempts, and those with a history of physical assault by an intimate partner have more than 2.5 times the risk of suicide attempts.…”
Section: Interpersonal Victimization and Suicidalitymentioning
confidence: 97%
“…Group 1 Group 2 Group 3 er regions of Brazil and the USA, which pointed men as the most involved in situations of community violence and more likely than women to experience robberies and violence by unknown persons 1,4,26,27 . Most men victimization by community violence can be explained from the perspective of different scientific fields such as epidemiology, sociology and psychology.…”
Section: Dimension 1 Dimensionmentioning
confidence: 99%
“…Interpersonal violence is considered a high-priority public health problem in different regions of the world and has been widely discussed by various sectors of society due to its impact on public safety indicators, on the daily lives of individuals and to the constant presence of victims in health services [1][2][3][4] . Every year, millions of people lose their lives and many others carry non-fatal injuries resulting from domestic and community violence.…”
Section: Introductionmentioning
confidence: 99%